Catalytic formal [4 + 1] isocyanide-based cycloaddition: an efficient strategy for the synthesis of 1H-cyclopenta[b]quinolin-1-one derivatives - Motaghi, Mila; Rominger, Frank (Organic & biomolecular chemistry, 2019)
An unprecedented catalytic isocyanide-based cycloaddition of alkyl and aryl isocyanides with (Z)-2-(2-hydroxy-2-alkylvinyl)quinoline-3-carbaldehydes was developed for the direct and efficient synthesis of 1H-cyclopenta[b]quinolin-1-one derivatives. On the basis of DFT calculations, a mechanism is proposed involving formal [4 + 1] cycloaddition of isocyanides, followed by imine-enamine tautomerization and air oxidation.
First published on 05 Dec 2018
Gesehen am 01.04.2019